Cytotoxicity of Mahanimbine from Curry Leaves in Human Breast Cancer Cells (MCF-7) via Mitochondrial Apoptosis and Anti-Angiogenesis - Yahya Hasan Hobani (Molecules, 2022)
Mahanimbine (MN) is a carbazole alkaloid present in the leaves of Murraya koenigii, which is an integral part of medicinal and culinary practices in Asia. In the present study, the anticancer, apoptotic and anti-invasive potential of MN has been delineated in vitro. Apoptosis cells determination was carried out utilizing the acridine orange/propidium iodide double fluorescence test. During treatment, caspase-3/7,-8, and-9 enzymes and mitochondrial membrane potentials (Δψm) were evaluated. Anti-invasive properties were tested utilizing a wound-healing scratch test. Protein and gene expression studies were used to measure Bax, Bcl2, MMP-2, and -9 levels. The results show that MN could induce apoptosis in MCF-7 cells at 14 µM concentration IC50. MN-induced mitochondria-mediated apoptosis, with loss in Δψm, regulation of Bcl2/Bax, and accumulation of ROS (p ≤ 0.05). Caspase-3/7 and -9 enzyme activity were detected in MCF-7 cells after 24 and 48 h of treatment with MN. The anti-invasive property of MN was shown by inhibition of wound healing at the dose-dependent level and significantly suppressed mRNA and protein expression on MMP-2 and -9 in MCF-7 cells treated with a sub-cytotoxic dose of MN. The overall results indicate MN is a potential therapeutic compound against breast cancer as an apoptosis inducer and anti-invasive agent.